Dielectric Properties of Lignocellulosic Fibers Reinforced Polymer Composites: Effect of Fiber Loading and Alkaline Treatment - Jayamani, E.; Sinin, Hamdan; Rahman, M.R.; Bakri, M.K.B. (Elsevier Ltd., 2015)
This research work focus on comparative studies of dielectric properties such as the dielectric constant, the dissipation and loss factor of four different types of composites made of lignocellulosic fibers with respect of fiber loading and alkali treatment. It has been observed that the dielectric constant, dissipation factor and loss factor progressively increases with increase in fiber loading and decreases with an increase in frequency. The dielectric properties of sisal/poly-lactic acid composites show higher values compared with other composites. This is due to the characteristics of lignocellulosic contents in the sisal fibers. The dielectric constant values were lower for fibers subjected to alkaline treatment.